THE EFFECT OF LABORATORY SERVICE QUALITY ON PATIENT SATISFACTION AT PUSKESMAS AJUNG, JEMBER REGENCY - Liansyah, Ahmad Hotip Ragil; Susanti, Indria Yuli; Saputra, Harmawan Teguh (Politeknik Negeri Ambon, 2026)
Introduction: Laboratory services are an essential component of primary healthcare as they support accurate diagnosis and treatment, while also influencing patient perceptions of service quality. However, issues such as long waiting times, limited facilities, and unclear communication may reduce patient satisfaction. Therefore, this study aims to examine the effect of laboratory service quality on patient satisfaction at Puskesmas Ajung, Jember Regency.Methods: This research employed a quantitative approach with a cross-sectional design using accidental sampling, involving 36 respondents who received laboratory services. Data were collected through a structured questionnaire based on service quality dimensions, including reliability, responsiveness, assurance, empathy, and tangibles, and were analyzed using validity and reliability tests and simple linear regression analysis.Results: The findings indicate that laboratory service quality has a positive and significant effect on patient satisfaction, as evidenced by a regression coefficient of 0.257 and a significance value of 0.000, which is lower than 0.05. The correlation coefficient shows a moderately strong relationship, while the coefficient of determination indicates that 31.1% of patient satisfaction can be explained by laboratory service quality. Conclusion and suggestion: It can be concluded that improving laboratory service quality, particularly in terms of service speed, clarity of information, staff professionalism, and facility comfort, will enhance patient satisfaction. Therefore, healthcare providers are encouraged to continuously improve service quality and facilities, while future researchers are advised to include additional variables and larger sample sizes to obtain more comprehensive results. Keywords: Laboratory Service Quality; Patient Satisfaction; Public Health Center; SERVQUAL